THE INFLUENCE OF STORYTELLING METHOD ON READING ABILITY OF SECOND GRADE MADRASAH IBTIDAIYAH STUDENTS: A PRE-EXPERIMENTAL STUDY (Pena Cendekia Insani, 2026)
This research aims to determine the effect of the storytelling method on the reading ability of second-grade students at MIS Al Amin Beringin. The research problem stems from the importance of strengthening reading skills in lower grades as a foundation for students' learning success. This study uses a quantitative approach with a one group pretest-posttest design. The research sample consisted of 26 students from class II-A for the 2025/2026 academic year. Data were collected through reading ability tests administered before and after the treatment. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and N-Gain. The research results showed that the average pretest score of 59.31 increased to 77.08 in the posttest, with an average difference of 17.77 points. The paired sample t-test yielded a Sig. (2-tailed) value of 0.000 < 0.05, thus the alternative hypothesis was accepted. The N-Gain value of 0.443 falls into the moderate category. These findings indicate that the storytelling method has a significant and quite effective impact on improving students' reading skills. This research implies the need for lower-grade teachers to use more communicative, narrative, and student-characteristic-aligned reading teaching methods. Storytelling can be applied as a practical strategy to improve reading accuracy, fluency, pronunciation, intonation, and comprehension of simple reading materials.